A short recent review on hybrid energy systems: Critical analysis and recommendations. (November 2022) - Farhat, Obeida; Khaled, Mahmoud; Faraj, Jalal; Hachem, Farouk; Taher, Rani; Castelain, Cathy
Abstract: Currently, the world is perceiving a change-over from its existing conventional energy sources to a future with optimized and inventive energy sources. Nowadays, the world is more and more oriented to the use of renewable energy sources to decrease the consumption form the conventional energy sources in particular the fuel energy. In addition, the use of renewable energy source decrease the impact of the conventional energy on the environment. For all these reasons, researchers are currently focusing on studies that implement and innovate methods for the purpose of optimizing and increasing the efficiency of existing renewable energy sources. Of the proposed methods are the hybrid systems. These systems are applicable in both residential and industrial sectors. However, hybrid systems can be applied to renewable energy, wind energy, fuel cell, Desalination, Heating, Ventilating, and Air Conditioning, Engines, Electric Vehicles, Heat Pump, Redrying, PV cells, Engines, Solar Cells, and many other systems. In this context, the aim of the present paper is to provide a short recent review focusing on the types and applications of hybrid renewable energy systems and hybrid recovery energy systems that are applied in industrial and residential sectors. Moreover, the environmental impact, cost and the efficiency will also be presented and discussed.